Implementation of Child Identity Card (KIA) Policy At The Population and Civil Registration Service of Palu City - Sussanti Sussanti; Daswati Daswati; Nasir Mangngasing (UIN Sunan Gunung Djati, 2024)
This study aims to determine the process of implementing the child identity card (KIA) policy at the Palu City Population and Civil Registration Service. The regulations governing the issuance of child identity cards (KIA) are regulated in the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards. The approach used in this study is qualitative with a descriptive approach. Qualitative research is a study that produces and manages descriptive data, such as interview and observation transcriptions. While descriptive is a research method used to examine the condition of natural objects, where researchers are key instruments, data collection techniques are carried out by triangulation (combination), data analysis is inductive, and qualitative research results emphasize meaning rather than generalization. The results of this study show that the implementation of the Child Identity Card (KIA) policy at the Palu City Population and Civil Registration Service has not gone as expected. From the two indicators put forward by Grindle (1980), namely policy content and policy context, there are several findings. In the policy content, there are several obstacles in the policy implementation process caused by several things such as the lack of benefits from the implementation of the child identity card policy felt by the Community and the child identity card which is not a priority for the Community to be made immediately. While in the policy context it shows that the cause of the child identity card policy not being implemented properly is because the strategy used is not supported by a sufficient budget and the Community's perception that the child identity card does not have any benefits that they can get.